Third report of Allochaetophoridae Reck, 1959 (Acari: Trombidiformes) based on the description of a new species from Iran - Mahdavi, Sayed Mosayeb; Asadi, Mahdieh (Zootaxa, 2015)
A new mite species Allochaetophora iranica sp. nov. (Tetranychoidea: Allochaetophoridae), is described and illustrated based on females and deutonymphs collected from Phragmites australis (Poaceae) in Iran (Kerman Province). This is the third report of the family Allochaetophoridae for the world and first report of it from Asia.